Coaching olympic athletes with sport psychology - Cogan, K. D. (Consulting Psychology Journal: Practice and Research, 2020)
This article focuses on a sport psychologist`s consulting experiences with Olympic athletes. As Olympic athletes progress through training and preparation each Olympic quadrennium, they are aware that a superior performance can make or break their athletic careers. In reality, Olympic success is not the life-or-death situation that some elite performers face, such as physicians or military personnel, but it certainly seems that way to those who have devoted their lives to athletic excellence. Because of the high stakes involved, the sport psychologists who assist the elite of the elite in coping with this competition face their own stress in performing under immense pressures. This article outlines the challenges, stressors, and mind-sets of athletes followed by the pressures faced by sport psychologists in the preparation for and competition at the Olympic Games. Best practices in providing sport-psychology services, such as the use of mindfulness, managing energy, and training with "What if?" scenarios ahead of time, are covered. The challenges of intervening in the height of performance pressure are addressed using examples during Olympic competition. The sport psychologist`s own reactions to unexpected issues as well as choice points in intervening with teams are then discussed. Finally, maintaining perspective and self-care in this constant high-performance environment are examined.